PTH-157 The prognostic impact of extracapsular lymph node involvement after neoadjuvant therapy and oesophagectomy. (22nd June 2015) - Lagarde, SM; Navidi, M; Sultan, J; Gisbertz, SS; van Laarhoven, HM; Meijer, SL; Immanuel, A; van Berge Henegouwen, MI; Griffin, M
Abstract : Introduction: In patients with oesophageal cancer, little attention has been paid to the biological significance of extracapsular lymph node involvement (LNI) in patients who underwent neoadjuvant treatment followed by oesophagectomy. Therefore, the aim of the present study was to assess the incidence, extent of extracapsular LNI and prognostic significance in a consecutive multicenter series of patients with cancer of the oesophagus or gastro-esophageal junction (GOJ) who underwent neoadjuvant chemo (radio) therapy followed by surgery. Method: From a prospectively collected database, a consecutive series of patients in two high volume centres in Europe was analysed. All patients with potentially curable adeno- or squamous cell carcinoma of the oesophagus or GOJ were treated with neoadjuvant chemotherapy or chemoradiation therapy followed by transthoracic oesophagectomy and two-field lymphadenectomy. Results: Between January 2000 and September 2013 a consecutive series of 704 patients underwent an oesophagectomy after neoadjuvant therapy. A median number of 28 (5–77) nodes was resected and identified. 347 (49.3%) patients had no evidence of lymph node metastases (ypN0). There were 357 (50.7%) patients with positive nodes (ypN1-N3). Extracapsular LNI was identified in 190 (53.2%) of lymph node positive patients. Five-year overall survival rates were 63% for N0 patients, 45% for patients with intracapsular LNI and 14% for patients with extracapsular LNI (p < 0.001). Multivariate analyses demonstrated that a higher ypT-stage, a higher ypN-stage, the presence of extracapsular LNI male gender, and a microscopically irradical resection were all independent prognostic factors. Conclusion: The presence of extracapsular LNI after neoadjuvant chemo (radiation) therapy identifies a subgroup of patients with a significantly worse long-term survival. Extracapsular LNI reflects a particularly aggressive biologic behaviour and has significant prognostic potential and should be considered for the future edition of the TNM staging system for oesophageal cancer. Disclosure of interest: None Declared.